Preparation of transversely isotropic test specimen of glass FRP composite - an innovative approach-I - A, Srihari Prasad; V, Balakrishna Murthy; V, Ramana K; G, Sambasiva Rao (Journal of Experimental Sciences, 2012)
FRP composites have attracted attention of researchers due to ever increasing demand for lighter and stronger materials from the industry, more so from aerospace and automotive sector. Researchers, particularly in academic institutions, are suffering due to non-availability of detailed information on fabrication techniques for preparing FRP test specimens that are equivalent to an analytical model. Accurate test specimen close to analytical model reduces the compulsion of going for unrealistic assumptions that takes the analysis away from reality. An easy to follow method to design, compute and achieve correct volume fraction is presented in this work. A technique for preparing and dismantling molds with commonly available materials is presented in detail. Using simple tools and tackles coupled with a few precautions followed as described herein, prospective researchers can fabricate FRP test specimen close to their requirement.